2007
DOI: 10.1080/07408170600729218
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of considering inventory in service parts logistics network design problems with time-based service constraints

Abstract: We study the integrated logistics network design and inventory stocking problem as characterized by the interdependency of the design and stocking decisions in service parts logistics. These two sets of decisions have been usually considered sequentially in practice, and the associated problems have been tackled separately in the research literature. The overall problem is typically further complicated due to time-based service constraints that provide lower limits for the percentages of demand satisfied withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Simultaneously, there are developments regarding the computational complexity of the intended class of optimization model (i.e., Single Item -Single Echelon Model). Candas et al (2007) has shown that the model could be efficiently solved within reasonable timeframes by using advanced heuristics solution methods. However, the potential economic value that could be generated by using detailed data is unaddressed in literature for the intended planning model.…”
Section: Data Aggregation Vs Disaggregated Data Usagementioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, there are developments regarding the computational complexity of the intended class of optimization model (i.e., Single Item -Single Echelon Model). Candas et al (2007) has shown that the model could be efficiently solved within reasonable timeframes by using advanced heuristics solution methods. However, the potential economic value that could be generated by using detailed data is unaddressed in literature for the intended planning model.…”
Section: Data Aggregation Vs Disaggregated Data Usagementioning
confidence: 99%
“…A simplified version of the model that incorporates its main characteristics is depicted in Appendix A. Briefly described, the model follows the optimization logic of Single Echelon -Single Commodity Model (Giani et al, 2004) with additional time based constraints (Candas et al, 2007). The optimization model is a Mixed Integer Program that uses the customer locations, part's unit price, demand rates, travel times, handling and transportation costs as input data.…”
Section: Spare Parts Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the design factors considered in the literature include logistic network design, capacity investment, part supplier selection, and transportation modes selection (see, e.g., [142,143,144,145,146]). The literature shows that a comprehensive inclusion of such design factors with the spare parts inventory optimization problem requires significant computational efforts.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Candas and Kutanoglu (2007), for instance, solve the joint problem by linearizing fill rate functions and then solving the resulting mixed integer linear programming formulation. Rappold and Van Roo (2009) use a two-step approach: the first step consists mainly of the facility location problem whereas the second step considers the spare parts inventories.…”
Section: Facility Location Problemmentioning
confidence: 99%